Modelo De Un Sistema Constructivo Eficiente Y Económico En Viviendas De Interés Social En El Cantón Huaquillas - Mora Bravo, Carlos Elías (2017)
This project proposes a MODEL of an efficient and economic construction system in housing of social interest of the canton Huaquillas. This research carried out a comparative analysis of the traditional construction systems that are applied in the city of Huaquillas and that limit the beneficiary to acquire this type of housing because of the high cost in the private housing estates, so they have to participate in the housing programs. Houses presented by the national government as a solution. The methodology used for this research is purely bibliographical from which the necessary information was obtained for the comparative analysis of the prefabricated construction systems such as the AVAN, SEMILLA and SALVY system with the traditional system, determining a new constructive system applying a combination of some items of the systems investigated. The results obtained from this research have as main objective to propose the solution to the problem, which consists of a new model of constructive system using some prefabricated items of the systems investigated to obtain an efficient, economic and comfort social housing; Which complies with the size of the house, air conditioning, accessibility and an adequate environmental management plan.